2021
DOI: 10.3390/cells10123323
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Modification of HMGB1 Disulfide Bonds in Stimulating and Inhibiting Inflammation

Abstract: High mobility group box 1 protein (HMGB1), a highly conserved nuclear DNA-binding protein, is a “damage-associated molecular pattern” molecule (DAMP) implicated in both stimulating and inhibiting innate immunity. As reviewed here, HMGB1 is an oxidation-reduction sensitive DAMP bearing three cysteines, and the post-translational modification of these residues establishes its proinflammatory and anti-inflammatory activities by binding to different extracellular cell surface receptors. The redox-sensitive signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 132 publications
(193 reference statements)
0
45
0
Order By: Relevance
“…With regards to HMGB1 secretion, it occurs via ER-independent secretory pathways and depends on its post-translational modifications such as acetylation and its redox state, specifically disulfide bonds ( Andersson et al., 2021 ; Kwak et al., 2020 ). In immune cells, its cytoplasmic translocation and subsequent release require acetylation in the nuclear localization sequence ( Magna and Pisetsky, 2014 ; Ramadan et al., 2017 ) via Janus kinases/signal transducer and activator of transcription-1 or poly(ADP-ribose) polymerase-1 pathway ( Lu et al., 2014 ; Yang et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to HMGB1 secretion, it occurs via ER-independent secretory pathways and depends on its post-translational modifications such as acetylation and its redox state, specifically disulfide bonds ( Andersson et al., 2021 ; Kwak et al., 2020 ). In immune cells, its cytoplasmic translocation and subsequent release require acetylation in the nuclear localization sequence ( Magna and Pisetsky, 2014 ; Ramadan et al., 2017 ) via Janus kinases/signal transducer and activator of transcription-1 or poly(ADP-ribose) polymerase-1 pathway ( Lu et al., 2014 ; Yang et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the situation that Cys106 is in the reduced state during necrosis and in the oxidation state during apoptosis. Furthermore, homo-dimerization of HMGB1 at Cys106 has been found in the nucleus and extracellular, but its biological significance remains unclear ( 21 ).…”
Section: Biological Function Of Hmgb1mentioning
confidence: 99%
“…Activated immune cells [macrophages, dendritic cells (DCs)] and tissue cells (endothelial cells neurons, astrocytes) actively secreted HMGB1 ( 21 ). The release of HMGB1 from the nucleus to the cytoplasm depends on the activation of the Janus kinase (JAK) signal transducer and activator of transcription 1 (STAT1) pathway, or the balance of the histone acetylase (HAT) activity and histone deacetylase (HDAC) activity, or the formation of disulfide HMGB1 via peroxidase I and II ( 14 , 21 ). Then HMGB1 was packaged in vesicles and released extracellular via lysosomal pathway ( 6 ).…”
Section: Biological Function Of Hmgb1mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it has been previously demonstrated that oxidative stress due to cigarette smoke exposure reduces HDAC2, HDAC3, and sirtuin 1 (SIRT1) expression/activity [ 11 , 12 , 13 ]. Agents such as metformin, resveratrol, and curcumin, enhancing SIRT1 deacetylase activity, lead to the decrease of extracellular HMGB1 release and the inhibition of HMGB1-dependent inflammation [ 14 ]. Depending on the nature of cellular insults and cytotypes, the release mechanisms of HMGB1 are controlled at various levels, including activation of transcription factors such as NF-κB and the nucleotide-binding oligomerization domain (NOD)-like receptor family pyrin domain containing protein three (NLRP3) inflammasome.…”
Section: Introductionmentioning
confidence: 99%